Diastereo- and Enantioselective Assembly of Spirooxindole Tetrahydroquinoline Skeletons through Asymmetric Binary Acid Catalyzed Hydride Transfer–Cyclization - Mao, Zhenjun; Mo, Fan; Lin, Xufeng (Synlett, 2016)
An efficient binary acid catalyzed asymmetric intramolecular tandem 1,5-hydride transfer/ring-closure reaction was achieved. The process is catalyzed by the combination of a chiral spirocyclic phosphoric acid and magnesium chloride to afford structurally diverse spirooxindole tetrahydroquinolines in good yields with high diastereo- and enantioselectivities.
Keywords: asymmetric catalysis; phosphoric acid; Lewis acid; spirooxindoles; quaternary stereocenter